South Sudan's New National Malaria Strategic Plan 2021-2025 is a Game Changer - Harriet Akello Pasquale (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
The Ministry of Health of the Republic of South Sudan has just approved an ambitious 5-year National Malaria Strategic Plan 2020-2025 to control and prevent malaria, the third since South Sudan became an independent country in 2011. The launching ceremony on the 11th December 2020 was attended by senior officials of the Ministry of Health, the World Health Organization, UNICEF and malaria implementing partners. The Undersecretary of the Ministry of Health reiterated his government's commitment to mobilise resources to combat malaria, despite the country's economic hardship and immense natural disasters, which have triggered a call for humanitarian assistance for the population seriously affected by floods.